Entrepreneurial orientation and performance of Nigerian banks: The mediating effect of teamwork - Otache, Innocent; Mahmood, Rosli (MCSER Publishing, Rome-Italy, 2015)
Business environment has become highly competitive, dynamic, and heterogenic.As a result, business organizations are expected to be inclined. Also, for corporate entrepreneurial activities to have greater impact on organizational performance, organizational members (employees) must work collaboratively as a team. It is against this background that this study investigated the relationship between entrepreneurial orientation and performance of commercial banks in Nigeria and the mediating effect of teamwork on the relationship. Data were collected from 297 bank managers through a self reported questionnaire.SmartPLS-SEM was used to analyse the data collected and test the hypotheses formulated.The results of the structural model indicated a positive and significant relationship between entrepreneurial orientation and performance.Further evaluation of the structural model showed that teamwork fully mediated the relationship between entrepreneurial orientation and organizational performance. Based on the findings, it was concluded that while entrepreneurial orientation may be positively related to organizational performance, its impact on organizational performance will be greater if employees work collaboratively as a team.